Internalisasi Nilai Empati Dan Kepedulian Sosial Melalui Kurikulum Cinta - Muhammad Rusydu R (Jurusan Tarbiyah STAI Al-Gazali Bone, 2026)
National education aims not only to educate the nation but also to shape the character ofstudents, fostering empathy and social awareness. However, the current educational realitydemonstrates a degradation of humanitarian values, characterized by increasingindividualism, minimal tolerance, and rampant bullying in schools. This situation demandsa more humanistic educational approach oriented toward the values of compassion. Thisarticle aims to examine in depth the internalization of empathy and social awareness throughthe